Demographic changes in the context of sustainable development: Poland against the background of the European Union countries: comparative analysis (Economic and Political Thought, 2017)
Sustainable development is one of the foundations on which the EuropeanUnion is based. For more than 20 years, it has also been a primary principleof Poland’s social and economic development. It may be measured withthe use of a number of indicators. The demographic issues are includedin the sustainable development concept. It concerns social aspects as wellas economic and environmental ones. The main objective of the paperis to discuss the issues of current demographic changes in the context ofsustainable social development in Poland as well as in other EU MemberStates. The time perspective is set for the period from 2004 to 2014. Theanalysis covers 25 Member States divided into two groups (EU-10, i.e.Member States that joined the EU on 1 May 2004, including Poland; andEU-15, i.e. the so-called old EU states). The theoretical part of the paper isbased on documents and literature on the discussed subject. The comparativepart applies sustainable development indicators most effectively reflectingthe demographic changes taking place (aging society issues) in the context ofsustainable social development.